Efektivitas Model Pembelajaran Inkuiri Terbimbing Pada Praktikum Asam Basa Dengan Pemanfaatan Indikator Alami Terhadap Hasil Belajar Siswa - Nurjanah, Mega Bintang (Journal of Chemistry Sciences and Education, 2024)
Research has been conducted on the effectiveness of guided inquiry learning model on acid-base lab with the utilization of natural indicators on student learning outcomes in class XI SMA Nusantara Plus. The purpose of this study was to determine the results of learning completeness during the learning process. This research used descriptive qualitative method. The sample in this study were students of class XI MIPA 1 totaling 30 students consisting of 14 male students and 16 female students. Data collection techniques are done through written tests. The research instrument used was a multiple-choice question sheet (multiple chooise) of 10 questions. The results showed that the number of students who achieved learning completeness was 83.30% (very good category) with an average score of 81.77. Based on these results, it can be concluded that the guided inquiry learning model is effective in using practicum-based acid-base material by utilizing natural indicators at Nusantara Plus High School on student learning outcomes.